Becoming and being DLP: Designated Liaison Persons' experience of the role in the Irish primary school†. Issue 1 (2nd January 2018) - Nohilly, Margaret
Abstract : This paper reviews the role of the Designated Liaison Person (DLP) for Child Protection in the Irish primary school context. This is a role assigned by the Board of Management to a person in the school who oversees all matters pertaining to child protection including reporting abuse, liaising with staff and outside agencies in relation to child protection and meeting parents as required. Given the responsibilities associated with the role, it is normally the Principal teacher in the school who undertakes the role. A study undertaken with a number of DLPs in a variety of schools of different size and type highlights the multifaceted nature of the role, the supports available to DLPs and the challenges in undertaking this responsibility. The responsibility of ensuring the DLP is taking the correct course of action in making a referral of abuse in relation to a child is highlighted in the findings. Recent updates in child protection legislation which will impact on child protection procedures and policy in the school environment are also considered in this paper.